Characteristics that Define a Successful Pharmacy Resident as Perceived by Residency Programs. Issue 10 (November 2015) - Jellinek-Cohen, Samantha P.; Cohen, Victor; Rab, Saba; Likourezos, Antonios
Purpose: To identify the subjective and objective characteristics that pharmacy residency programs use to define a successful resident and to determine what percentage of their 2009-2010 residency class they felt were successful. Methods: An electronic survey was sent via e-mail to all residency program directors (RPDs) of postgraduate year 1 (PGY1) and postgraduate year 2 (PGY2) pharmacy residency programs in the United States. A 3-part survey instrument was developed following validation of questions for clarity and reliability using a pilot survey. Respondents were asked to rank the importance of 20 subjective characteristics for a resident to possess in order to be considered successful and the importance of different objective measurements of accomplishment in the definition of a "successful" resident using a Likert scale where 1 = not at all important, 2 = some importance, 3 = very important, and 4 = critical . Results: Of the 1, 081 surveys sent to RPDs, 473 respondents answered at least one question, yielding a response rate of 43.8%. The most critically important subjective characteristics in defining a successful resident as ranked among PGY1 residency programs are dependability, professionalism, self-motivation/initiative, and work ethic. PGY2 programs ranked clinical knowledge and skills, critical thinking, and dependability as the most important. The most critically important objective characteristic in defining a successful resident as ranked among both PGY1 and PGY2 programs is obtaining a clinical position. The majority of PGY1 and PGY2 respondents felt that 76% to 100% of their 2009-2010 residency class was successful based on the characteristics they rated most important. Conclusion: Identification of the characteristics that pharmacy residency programs use to define success will allow them to identify predictors of success and optimal methods of selecting residents who possess these characteristics.